Sports medicine: Performance-enhancing drugs - Gregory, A. J. M.; Fitch, R. W. (Pediatric Clinics of North America, 2007)
Performance-enhancing drugs, ergogenic aids, or sports supplements have been a part of sports since sporting competition began and likely always will be. Considered cheating by purists and necessary by some athletes, we must accept the fact that they are used, understand why they are used, and study how to prevent their use to institute change. This article summarizes current information regarding the use of performance-enhancing drugs in young athletes and provides proven prevention strategies for instituting a program in your local schools.